Airway persistence by the emerging multi‐azole‐resistant Rasamsonia argillacea complex in cystic fibrosis. Issue 9 (20th June 2018) - Abdolrasouli, Alireza; Bercusson, Amelia C.; Rhodes, Johanna L.; Hagen, Ferry; Buil, Jochem B.; Tang, Alison Y. Y.; de Boer, Leonard L.; Shah, Anand; Milburn, Andrew J.; Elborn, J. Stuart; Jones, Andrew L.; Meis, Jacques F.; et al.
Summary: Infections caused by Rasamsonia argillacea complex have been reported in various clinical settings. Cystic fibrosis (CF) is one of the main underlying conditions. An observational cohort study of CF patients with Rasamsonia in respiratory samples was conducted. Eight isolates from 6 patients were identified as R. argillacea complex and tested for antifungal susceptibility. All isolates had high MICs to voriconazole and posaconazole and low MECs to echinocandins. Four patients experienced lung function decline in the year preceding first Rasamsonia isolation. This continued in the year following first isolation in 3 out of 4 cases. Antifungal therapy was initiated in 2 patients, to which only one exhibited a clinical response. Three out of 6 patients died within 3 years of isolating Rasamsonia . Genotyping suggests that similar genotypes of Rasamsonia can persist in CF airways. Consistent with other fungi in CF, the clinical impact of airway colonisation by Rasamsonia is variable. In certain patients, Rasamsonia may be able to drive clinical decline. In others, though a clear impact on lung function may be difficult to determine, the appearance of Rasamsonia acts as a marker of disease severity. In others it does not appear to have an obvious clinical impact on disease progression.